TRANSFORMING GROWTH FACTOR Β IN BLOOD SERUM AND BRONCHOALVEOLAR LAVAGE FLUID IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - E. A. Surkova; N. A. Kuzubova; T. P. Ses’; N. V. Egorova; Areg A. Totolian (Медицинская иммунология)
Abstract. Progressive obstruction and lung tissue remodeling comprise an important feature of the airways in COPD patients. The main processes involved in tissue remodeling in COPD are protease/antiprotease, oxidant/antioxidant imbalances, like as inflammatory and fibrotic events that contribute to development or progression of disease. TGFβ is a multifunctional growth factor that regulates synthesis of extracellular matrix proteins, primarily collagen and fibronectin, thus inducing fibrosis of respiratory ways. The aim of our study was to determine levels of TGFβ in serum and bronchoalveolar lavage fluid (BALF) of COPD patients. All the patients with COPD had increased levels of TGFβ in serum, as compared with subjects without COPD (p < 0.01), but there was no difference in TGFβ concentration between patients at different stages of disease. Increased phagocytic activity of blood monocytes was found in 81% of COPD patients, as compared to controls. Phagocytosis of apoptotic Tcells and bacterial infection of monocytes leads to increased secretion of TGFβ and it may cause higher levels of TGF β in peripheral blood. TGFβ concentration in BALF of patients at stage III of disease was higher than in the patients at stage II (p < 0.05). The level of TGFβ in BALF directly correlates with number of alveolar macrophages (r = 0.39; р = 0.03). These data indicate that TGFβ is involved in chemotaxis of macrophages in COPD patients’ airways. We conclude that increased secretion of TGFβ by peripheral blood monocytes may be a result of their high phagocytic activity. Hence, TGFβ mediates interactions between the two main components underlying lung tissue remodeling, i.e. fibrosis of respiratory airways, and development of emphysema in COPD.